Effects of traditional Chinese exercises on brain-derived neurotrophic factor in middle-aged and older adults: A systematic review and meta-analysis of randomized controlled trials - Jianyu Gan; Jiya He; Kaixiang Zhou; Zhangyuting Shang; Gengxin Dong; Dapeng Bao; Junhong Zhou (Journal of Exercise Science & Fitness)
Background/Objectives: Brain-derived neurotrophic factor (BDNF) may help middle-aged and older adults resist age-related neurodegenerative conditions and psychiatric disorders. Recent studies suggested that Traditional Chinese exercises (TCEs) may be a promising strategy to improve the BDNF levels of these populations, while the effectiveness has yet to be definitively confirmed due to the variances in the study designs and observations. Therefore, this systematic review and meta-analysis aimed to examine the effects of TCEs intervention on BDNF in middle-aged and older adults. Methods: The search was conducted in November 2024 in seven Chinese and English databases. Two reviewers independently reviewed the search results, extracted the data, and assessed the risk of bias and certainty of evidence. Meta-analyses and meta-regressions were performed to determine the overall effect size and the impact of potential moderators. Results: Ten publications consisting of 543 participants were included. The overall effect size of TCEs on BDNF was large and significant [Hedges'g = 0.82, 95 % CI (0.55, 1.09), p < 0.01]. Subgroup analysis revealed that the effect size was non-significant for participants with mild cognitive impairment (MCI) (p = 0.08), while significant for participants with normal cognitive function (p < 0.01). In the meta-regression, moderators such as the mean age, sex, and baseline BDNF levels of participants, as well as total TCEs time were not associated with outcome variables. The certainty of the evidence was assessed as moderate. Conclusions: This systematic review and meta-analysis indicates that TCEs intervention could increase the levels of BDNF in middle-aged and older adults with normal cognitive function. Systematic review registration: www.crd.york.ac.uk/PROSPERO/, identifier: CRD42023484121.